2022
DOI: 10.1155/2022/2557107
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Adsorption Performance and Adsorption Mechanism of Graphene Oxide by Red Sandstone in Aqueous Solution

Abstract: In order to deal with the increasingly serious pollution of graphene oxide (GO) to the environment. In this paper, the use of red sandstone to treat GO-contaminated aqueous solution is proposed for the first time, and the adsorption capacity and adsorption mechanism of red sandstone to GO are discussed. The controlled variable method was used to explore the optimal pH, concentration, and quality of red sandstone for GO aqueous solution. The adsorption isotherm, thermodynamics, and adsorption kinetics were fitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…[ 79 ] found that GO adsorption on red sandstone increased with increasing temperature under the same GO concentration. This was mainly due to the enhancement of the activity of GO molecules in the aqueous solution, increasing the possibility of GO particles contacting the adsorption active sites [ 79 ]. Ref.…”
Section: Resultsmentioning
confidence: 99%
“…[ 79 ] found that GO adsorption on red sandstone increased with increasing temperature under the same GO concentration. This was mainly due to the enhancement of the activity of GO molecules in the aqueous solution, increasing the possibility of GO particles contacting the adsorption active sites [ 79 ]. Ref.…”
Section: Resultsmentioning
confidence: 99%
“…The modified CSAC particles contained a large number of functional groups that are easily adsorbed and are good carrier materials for Fenton catalysts. The peaks near 3436.528 cm −1 were mainly due to the stretching vibration of O-H bonds in hydroxyl and carboxyl groups [24,25]. The absorption peaks at 1734.656 cm −1 and 1560.612 cm −1 were generated by the stretching vibration of C=O and aryl ring skeleton [24,26].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 99%
“…The peaks near 3436.528 cm −1 were mainly due to the stretching vibration of O-H bonds in hydroxyl and carboxyl groups [24,25]. The absorption peaks at 1734.656 cm −1 and 1560.612 cm −1 were generated by the stretching vibration of C=O and aryl ring skeleton [24,26]. The peaks at 1091.030 cm −1 corresponded to C-O telescopic vibration peaks [24].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 99%
See 1 more Smart Citation